2021
DOI: 10.1038/s41416-021-01366-1
|View full text |Cite
|
Sign up to set email alerts
|

G-protein subunit gamma-4 expression has potential for detection, prediction and therapeutic targeting in liver metastasis of gastric cancer

Abstract: Liver metastasis of gastric cancer is the most common for hematogenous metastases and so fatal, that the identification of novel markers and targets for therapy are crucial. We conducted transcriptome analyses between synchronous liver metastasis, primary tumor, and adjacent tissues from four patients with metastasis confined to the liver to discover that GNG4 upregulated substantially in primary gastric cancer tissues. Quantitative RT-qPCR assay for 300 gastric cancer patients revealed that higher levels of G… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 60 publications
2
16
0
Order By: Relevance
“…The overall survival rate of the igh GNG4 expression group was significantly lower than low GNG4 expression group. A similar result has been shown in liver cancer 12 and also other cancers. 11,26 As for lung cancer, GNG4 expression had also been demonstrated to be overexpressed in NSCLC.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The overall survival rate of the igh GNG4 expression group was significantly lower than low GNG4 expression group. A similar result has been shown in liver cancer 12 and also other cancers. 11,26 As for lung cancer, GNG4 expression had also been demonstrated to be overexpressed in NSCLC.…”
Section: Discussionsupporting
confidence: 88%
“…8 Previous studies have found that GNG4 expression is elevated in a variety of tumors and is related to the poor prognosis of these patients, including bladder, liver, breast and non-small-cell lung cancers. 7,[9][10][11][12] Most studies confirmed the significance of high GNG4 expression by analyzing the correlation of sequencing data and clinical data and their related mechanisms. Maina et al confirmed that GNG4 is the target gene of VHL and is related to the response pathways.…”
Section: Introductionmentioning
confidence: 98%
“…The binding of the lipid S1P (Sphingosine-1-phosphate) to the Sphingosine-1-phosphate receptors (S1PR1, S1PR2, S1PR3, S1PR4 and S1PR5) triggers different pathways involved in cell differentiation, proliferation, angiogenesis and migration [ 66 ]. Upregulation of the guanine nucleotide binding-protein gamma subunit 4 protein ( GNB4 ) was significantly associated with primary tumor, nodal metastasis, histological grade, vascular invasion and mitotic rate [ 67 , 68 ]. High expression of EDNRA is associated with metastasis and poor outcome in patients with advanced bladder cancer [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…GNG4 is also used as a biomarker in gastric cancer, especially in liver metastasis of gastric cancer. High levels of GNG4 in primary tumor tissue have been reported to be associated with short overall survival times and the likelihood of liver metastasis recurrence [17]. Notably, GNG4 is not only a candidate biomarker for the diagnosis of synchronous metastasis and the prediction of metachronous metastasis but may also be a predictive factor concerning 5FU, a representative pyrimidine drug [17].…”
Section: Introductionmentioning
confidence: 99%
“…High levels of GNG4 in primary tumor tissue have been reported to be associated with short overall survival times and the likelihood of liver metastasis recurrence [17]. Notably, GNG4 is not only a candidate biomarker for the diagnosis of synchronous metastasis and the prediction of metachronous metastasis but may also be a predictive factor concerning 5FU, a representative pyrimidine drug [17]. GNG4 was also demonstrated to be the key element of the colorectal carcinoma (CRC) tumor mutation burden (TMB), which is essential information in the ICB therapy of CRC [18].…”
Section: Introductionmentioning
confidence: 99%